The Use of Animated Sex Education Videos to Support Socialization Skills in Kindergarten Children - Salsabilla, Zahra; Nurhafizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Lack of understanding of socialization skills in children in kindergarten is caused by limited variations in learning media and lack of knowledge from teachers regarding its importance. As a result, interactions between boys and girls tend to occur without any boundaries that are in accordance with the child's gender. The purpose of this study was to determine the effect of the use of animated sex education videos on socialization skills in kindergarten. This quantitative study used an experimental method. The population in the study consisted of early childhood children in state kindergartens, totaling 277 children. The sampling technique used in this study was purposive sampling. The total sample of the study was 40. The methods used in collecting data were observation and testing. The instruments used in collecting data were observation sheets and test questions. The data analysis technique used in this study was to compare the differences between the two average values, so it was carried out with a t-test. The results of the study showed that the average value of children's socialization skills before being given treatment in the form of animated sex education videos was 21.60, and the average value of children's socialization skills after being given treatment in the form of animated sex education videos was 29.65. The results of the hypothesis test show the influence of the use of animated sex education videos on children's socialization skills in kindergarten. It is concluded that the use of animated sex education videos can improve children's socialization skills in kindergarten. The implication of this research is that the use of animated sex education videos can help children learn boundaries according to their gender.